Occurrence of domatia in Angiospermae - Barros, Myrthes A.A. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
The present paper deals with the occurrence of domatia in the leaves of Annona muricata L. The domatia were generally situated on the base of the nervure of 1st and 2nd order. The type is that the "en touffe de poils", according to the classification of CHEVALIER & CHESNAIS (1941). The leaves were examinated in boch sides and at the junction of the blade with the petiole. The material was collected in the campus of Escola Superior de Agricultura "Luiz de Queiroz". The occurrence or not of domatia, the type, localization, size, form, and other characteristics wete studied, as well.